An outbreak due to Candida auris with prolonged colonisation and candidaemia in a tertiary care European hospital. Issue 7 (8th June 2018) - Ruiz‐Gaitán, Alba; Moret, Ana M.; Tasias‐Pitarch, María; Aleixandre‐López, Ana I.; Martínez‐Morel, Héctor; Calabuig, Eva; Salavert‐Lletí, Miguel; Ramírez, Paula; López‐Hontangas, José L.; Hagen, Ferry; Meis, Jacques F.; Mollar‐Maseres, Juan; et al.
Summary: Multidrug‐resistant Candida auris has emerged as a cause of insidious hospital outbreaks and complicated infections. We present the analysis of an ongoing C. auris outbreak including the largest published series of C. auris bloodstream infection. All C. auris‐ positive patients from April‐2016 to January‐2017 were included. Environmental, clinical and microbiological data were recorded. Definitive isolate identification was performed by ITS‐rDNA sequencing, and typing by amplified fragment length polymorphism fingerprinting. One hundred and forty patients were colonised by C. auris during the studied period (68% from surgical intensive care). Although control measures were implemented, we were not able to control the outbreak. Forty‐one invasive bloodstream infections (87.8% from surgical intensive care) were included. Clinical management included prompt intravascular catheter removal and antifungal therapy with echinocandins. All isolates were fluconazole‐ and voriconazole‐resistant, but echinocandin‐ and amphotericin B‐susceptible. Thirty‐day mortality rate was 41.4%, and severe septic metastasis as spondylodiscitis and endocarditis were observed in 5 patients (12%). C. auris was also recovered from inanimate patient surroundings and medical equipment. Despite antifungal treatment, high mortality and late complication rates were recorded. Molecular typing suggested a clonal outbreak different from those previously published.